Разговорная речь в системе литературного языка и разговорность в истории русской художественнои речи - СИРОТИНИНА, ОЛЬГА Б. (Stylistyka, 2021)
In the research on the Russian colloquial language in the second half of the 20th с. there appeared three points of view. Тhе first of them (Laptieva 1966; 1976) identifies the colloquial language with the oral (uncodified) variety of the literary language, as opposed to the codified literary language. Тhе second opposes the colloquial language to the literary language as а whole, recalling the contrast "formal/ /informal" (Ziemskaya 1968; 1987). The third considers it to Ье а functional style of the literary language(Vasileva 1976) or а functional variety of the language in question (Sirotinina 1969; 1974). Russian linguists argue that there is а basic difference Ьetween the living colloquial language and the colloquial- Шее stylization in artistic texts (Vinogradov 1930; Sirotinina 1965; Vinokur 1977). Colloquiality as an aesthetic category consists in creating, Ьу the author, the impression of colloquial speech. Тhе paper discusses that category in the blstory of the Russian artistic language from Pushkin to the contemporary writers.